AWS certified cloud practitioner exam guide : build your cloud computing knowledge and upskill yourself as an AWS certified Cloud Practitioner (CLF-C01) - Daswani, Rajesh (Packt Publishing, 2023)
Develop proficiency in AWS technologies and validate your skills by becoming an AWS Certified Cloud Practitioner About This Audiobook Develop the skills to design highly available and fault-tolerant solutions in the cloud Learn how to adopt best-practice security measures in your cloud applications Achieve credibility through industry-recognized AWS Cloud Practitioner certification In Detail Amazon Web Services is the largest cloud computing service provider in the world. Its foundational certification, AWS Certified Cloud Practitioner (CLF-C01), is the first step to fast-tracking your career in cloud computing. This certification will add value even to those in non-IT roles, including professionals from sales, legal, and finance who may be working with cloud computing or AWS projects. If you are a seasoned IT professional, this certification will make it easier for you to prepare for more technical certifications to progress up the AWS ladder and improve your career prospects. The book is divided into four parts. The first part focuses on the fundamentals of cloud computing and the AWS global infrastructure. The second part examines key AWS technology services, including compute, network, storage, and database services. The third part covers AWS security, the shared responsibility model, and several security tools. In the final part, you'll study the fundamentals of cloud economics and AWS pricing models and billing practices. Complete with exercises that highlight best practices for designing solutions, detailed use cases for each of the AWS services, quizzes, and two complete practice tests, this CLF-C01 exam study guide will help you gain the knowledge and hands-on experience necessary to ace the AWS Certified Cloud Practitioner exam. Audience If you're looking to advance your career and gain expertise in cloud computing, with particular focus on the AWS platform, this book is for you. This guide will help you ace the AWS Certified Cloud Practitioner Certification exam, enabling you to embark on a rewarding career in cloud computing. No previous IT experience is essential to get started with this book, since it covers core IT fundamentals from the ground up.